Implementation of a Low-Carbohydrate Diet Improves the Quality of Life of Cancer Patients – An Online Survey - Tulipan, Julia; Kofler, Barbara (Frontiers in Nutrition, 2021)
Background: The ketogenic diet (KD), a high-fat low-carbohydrate diet, has gained in popularity in recent years, which is reflected by an increasing number of scientific articles, books, websites, and other publications related to low carbohydrate (LC) diets and KDs. Numerous preclinical studies in different animal models of cancer have examined the effect of KDs on cancer growth, but no large randomized controlled studies or prospective cohort studies are available for human cancer patients. Evidence supporting the use of KDs as an adjunct to traditional cancer therapy has come predominantly from anecdotes and case reports. The first KD clinical trials in patients with glioblastoma revealed good acceptance and a possible anti-tumor effect. Metabolic therapy options such as the KD are not yet part of the standard of care in cancer patients. However, many cancer patients have begun implementing a KD or LC diet on their own. The aim of the present study was to gather information, via an online questionnaire, about how cancer patients go about implementing a KD or LC diet, what resources they rely on, whether they perceive benefits from the diet on quality of life (QoL), and what factors influence feasibility and adherence to the diet. Method: Recruitment of participants was carried out via social media platforms, forums and cooperating physicians (April 2018 through November 2018). To be eligible for the study, participants had to be diagnosed with cancer and on a KD or LC diet at the time of participating in the study or been on a KD or LC diet during cancer treatment. Study participants were asked to fill out an online questionnaire. The questionnaire was divided into four parts and contained a total of 64 questions. The questions were focused on the current health status of the participant, type of cancer, time since diagnosis, and treatment regimen. In addition, questions addressed social support, extent of professional counseling, food preferences and QoL. Results: A total of 96 participants (77 F, 17 M) submitted the questionnaire, of which 94 were included in the final data analysis. Ages ranged between 24 and 79 years (mean 50.1 ± 12.1 years). In 73.4% of the participants, the tumor had not formed metastases at the time of initial diagnosis. Twenty-four (26%) participants had a PET-positive tumor, 8 (9%) a PET-negative tumor, and the remainder (66.0%) did not report a PET scan. Eighty seven percent had undergone surgery in the course of their cancer treatment. The most frequent tumor type was breast cancer, followed by cervical cancer, prostate cancer, colorectal cancer and melanoma. Fifty nine percent of the study participants stated that they followed a KD during cancer therapy, 21% followed a low carbohydrate/high fat (LCHF) diet and 12% followed a low glycemic index (LOGI) diet. Sixty nine percent reported an improvement of QoL because of the diet. Almost half of the study participants sourced their initial information on KDs and LC diets from the internet. We found a significant correlation between weight loss upon implementation of a KD and the extent of overweight (p < 0.001). Weight loss in already lean participants was not reported. Overall, 67% of the participants found long-term adherence to the diet to be “easy” and 10.6% described it as being “very easy.” Participants who like fatty foods tended to perceive the diet as being easier to follow (p = 0.063). Conclusion: The KD or LC diet improved self-reported QoL in more than two-thirds of study participants. The KD had a normalizing effect on body weight. The majority of the participants rated the diet as easy or very easy to follow long term. There was an obvious gap between patients' desire for professional dietary counseling and what is currently offered by health care providers. In the future, efforts should be made to invest in nutrition experts who are trained in the KD to support cancer patients with implementation of a KD.